Hubungan Asesmen Geriatri Terintegrasi dan Komunikasi Efektif Menuju Asuhan Keperawatan Holistik dengan Perilaku Caring Perawat sebagai Variabel Intervening di Rumah Sakit Islam Siti Khadijah Kota Palembang - Pravitasari Pravitasari; Ratna Indrawati; Anastina Tahjoo (NUCLEUS, 2023)
In the world of health, Holistic Nursing Care is a standard with a multi-disciplinary approach through integrated and holistic assessment. Geriatric patients have complex needs that must be identified to address the needs that must be met by a hospital service to provide patient survival, quality of life and satisfaction. Holistic nursing care is influenced by several variables such as integrated geriatric assessment and effective communication. In addition to these two variables, there are other variables that can affect this relationship, one of which is the caring behavior of nurses. The purpose of this study was to analyze the relationship between Integrated Geriatric Assessment and Effective Communication of Holistic Nursing Care with Nurse Caring Behavior as Intervening Variables at Siti Khadijah Islamic Hospital, Palembang City. This research is explanatory research with a quantitative approach in the form of causality using 7 hypotheses with a sample of 80. The conclusion in this study is that there is a significant relationship between integrated geriatric assessment and effective communication on nurse caring behavior and holistic nursing care, besides that caring behavior turns out to be able to Intervene a significant relationship between integrated geriatric assessment and effective communication of holistic nursing care. Meanwhile, another significant relationship is between the caring behavior of nurses and holistic nursing care at Siti Khadijah Islamic Hospital, Palembang. The theoretical implications of this study will prove the effect of research variables and managerially will further improve the evaluation system for the quality of nursing care for geriatric services in hospitals and the overall management of geriatric patients for healthy old age.